Pathophysiology of diverticular disease. (3rd July 2018) - Schieffer, Kathleen M.; Kline, Bryan P.; Yochum, Gregory S.; Koltun, Walter A.
ABSTRACT: Introduction : Inflammation of diverticula, or outpouchings of the colonic mucosa and submucosa through the muscularis layer, leads to diverticulitis. The development of diverticular disease, encompassing both diverticulosis and diverticulitis, is a result of genetic predisposition, lifestyle, and environmental factors, including the microbiome. Areas covered : Previous reports implicated genetic predisposition, environmental factors, and colonic dysmotility in diverticular disease. Recent studies have associated specific host immune responses and the microbiome as contributors to diverticulitis. To review pertinent literature describing pathophysiological factors associated with diverticulosis or diverticulitis, we searched the PubMed database (March 2018) for articles considering the role of colonic architecture, genetic predisposition, environment, colonic motility, immune response, and the microbiome. Expert commentary : In the recent years, research into the molecular underpinnings of diverticular disease has enhanced our understanding of diverticular disease pathogenesis. Although acute uncomplicated diverticulitis is treated with broad spectrum antibiotics, evaluation of the microbiome has been limited and requires further comprehensive studies. Evidence suggests that a deregulation of the host immune response is associated with both diverticulosis and diverticulitis. Further examining these pathways may reveal proteins that can be therapeutic targets or aid in identifying biological determinants of clinical or surgical decision making.